Severe coronary vasospasm associated with hyperthyroidism causing myocardial infarction. Issue 6 (December 1995) - Masani, N. D.; Northridge, D. B.; Hall, R. J.
Abstract : A 48 year old woman presented with angina after an anterior myocardial infarction and was found to be hyperthyroid. Coronary angiography showed a stenosis of the left coronary os and a long, severe stenosis of the left anterior descending artery which was partially relieved by glyceryl trinitrate. Three months later, after radioactive iodine treatment had rendered her euthyroid, repeat coronary angiography showed entirely normal coronary arteries. This unusual case establishes an association between hyperthyroidism and coronary vasospasm resulting in myocardial infarction.